Activated Carbon from Coffee (Coffea Arabica L.) Husk Impregnated with ZnCl2 dan CaCl2 for the Adsorption of Tofu Wastewater - Irda Mayasopa; Vera Viena; Irda Yunita; Dewi Mulyati (Universitas Serambi Mekkah, 2024)
Tofu wastewater effluent contained high value of BOD, COD, and suspended solids which needed treatment before disposed to environment. The research aims to study the adsorption of BOD and COD in tofu wastewater using chemically impregnated carbon derived from coffee husks (Coffea Arabica L.). The Arabica coffee husk carbon (ACHC) activated with ZnCl2 0.1 N and CaCl2 0.1N for 3 hours. Carbon characterization compared with Indonesian standard of SNI No.06-3730-1995, and the surface area was examined by Fourier transform infrared spectroscopy (FTIR). The results showed that the moisture and ash content characteristics has met the Indonesian standard, but the iodine adsorption capacity was decreased with longer activation time. The highest iodine adsorption recorded at 888.37 mg/gr adsorbent using ZnCl2 0.1 N at 1 h activated time. The BOD and COD removal efficiency were 88% and 25%, for ACHC with ZnCl2 0.1N; Meanwhile carbon with CaCl2 0.1N has a removal efficiency 66% and 24% for BOD and COD, respectively. In conclusion, the variation of chemical activators and the longer contacted time gave significant effect on the removal of pH, BOD and COD from tofu wastewater. To obtain optimum COD adsorption efficiency in wastewater treatment, other factors such as the impregnation ratio, the activators concentration, the mixing time, and its combination method were needed further investigation.